Using transformational leadership to enhance the development of corporate strategy focused on a community’s common interests - Veríssimo, José Manuel (2012)
Little systematic research has been conducted to advance understanding of how transformational leadership enhances the development of corporate strategy focused on a community’s common interests. Using data from 50 Portuguese firms, we examined the role played by transformational leadership and its four dimensions—namely, idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—as well as ethical integrity in firms’ strategic orientation to corporate social responsibility. The results indicated that transformational leadership is significantly positively related to a firm’s strategic orientation to corporate social responsibility. However, leaders’ ethical integrity was not significantly linked to the adoption of corporate social responsibility practices. These findings suggest that further research is needed in regard to leaders’ ethical integrity and firms’ social responsibility orientation. Practitioners may also benefit from these findings by using them to transform themselves into “truly transformational leaders” who incorporate corporate social responsibility as a core strategic value within their firms.